1993
DOI: 10.1073/pnas.90.19.8817
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic mouse model of malignant skin melanoma.

Abstract: Tyr-SV40E transgenlc mice are spedflcay susceptbl to meanma due to expresion of the oncogene in pigment ceDs. Mice of the more nes die young of early-onset eye meanmas, when skin menas are stfll infrequent and benig. To surmount this oa, in from donors oftwo high-cepiblitlines was grafted to hosts of a low-septibi line of the same inbred strain, thereby enabling the skin to outlive the donors and continue to grow in hmmunocompetent but tolerant hosts. Unexpectedly, donor pIgment cells in all the grafts soon s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 29 publications
1
41
0
Order By: Relevance
“…Acquired or inherited mutations that alter stromal-cell function can release the suppression placed on context-inhibited malignant cells. Literature that spans more than a century has shown that inflammation associated with tissue wounding can produce tumours (REFS [35][36][37][38] and references therein)…”
Section: Activated Stroma As a Carcinogenmentioning
confidence: 99%
“…Acquired or inherited mutations that alter stromal-cell function can release the suppression placed on context-inhibited malignant cells. Literature that spans more than a century has shown that inflammation associated with tissue wounding can produce tumours (REFS [35][36][37][38] and references therein)…”
Section: Activated Stroma As a Carcinogenmentioning
confidence: 99%
“…Melanomas have been induced by carcinogenesis protocols but arise with low penetrance, long latencies and limited metastatic potential (Berkelhammer and Oxenhandler, 1987). Mintz and Silvers (1993) have produced a transgenic mouse melanoma model by the melanocyte-speci®c tyrosinase-directed expression of the SV40 early region (small and large T antigens). These mice develop ocular melanomas and, to a lesser extent, cutaneous melanomas.…”
Section: Building a Mouse Model For Malignant Melanomamentioning
confidence: 99%
“…The melanocytic lesions progressed to malignant melanoma in all skin grafts from the more susceptible of two transgenic donor lines tested, and in one-fourth of the grafts from another line; no melanomas of host onrgin developed. We have proposed that the induction of this maliancy in susceptible skin by wound healing is merely a caricature or exaggeration of the same basic biological and molecular events as ordinarily underlie the genesis of melanoma, without skin grafting, and that the exaggeration makes those events more accessible to analysis (3).…”
mentioning
confidence: 99%
“…This problem was recently overcome, and malignant skin melanomas were obtained, by taking advantage experimentally of the fact that different inbred lines of the mice differ in level of expression of the transgene and hence in degree of susceptibility to melanoma; yet all are members of the same standard strain, C57BL/6. Thus, by grafting skin from high-susceptibility transgenic donors to low-susceptibility transgenic hosts, the skin outlived the donors in immunocompetent hosts tolerant of the transgene product (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation